Determining Factors in Application of Green Accounting at Public Hospitals - Muhammad Hasyim Ashari; Umi Muawanah; Oyong Lisa (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Abstract The application of green accounting in public hospitals (RSUs) in Malang Raya must be based on financial, social and environmental activities, as a form of economic, social and environmental responsibility. This of course requires management's understanding of green accounting, and hospital management work experience, as well as considering the organizational size of the hospitals. The purpose of this study was to analyze and determine the effect of management's understanding of green accounting, organizational size and work experience either partially or simultaneously on the application of green accounting in public hospitals in Malang Raya, as well as the percentage level of the influence of research variables on the application of green accounting at public hospitals in Malang. This survey research uses a multivariate correlation approach, namely causal correlation using linear regression test. The variables used are management's understanding of green accounting, organizational size, and work experience as the independent variable and the application of green accounting as the dependent variable. The sampling method used is probability sampling with stratified sampling, so that 36 research samples were collected from a population of 40 RSUs. The novelty of this research is the addition of work experience variables, in addition to the variables of management's understanding of green accounting and the size of the general hospital organization. The results showed that simultaneously, the variables of management's understanding of green accounting, organizational size and work experience had an effect on the application of green accounting in public hospitals in Malang Raya. In fact, the effect of the variable management understanding of green accounting, organizational size and work experience on the application of green accounting variable is 38.5% and the remaining 61.5% is influenced by other variables besides the variables in this study. However, partially the variables of management's understanding of green accounting and organizational size that affect the application of green accounting in public hospitals in Malang Raya, while the work experience variable does not affect the application of green accounting in public hospitals in Malang Raya.